Plant galls of the Western United States - Russo, Ron (Princeton field guides., 2021)
A photographic guide to 536 species of plant galls found west of the RockiesBeautiful and bizarre, plant galls are growths of various shapes, sizes, and colors produced in response to invading organisms. Describing 536 species of galls and their causative agents, Plant Galls of the Western United States explores this unique realm with stunning photos and fascinating information about the life cycles of the organisms involved. Often species-specific, plant galls can be shaped like stars, baskets, clubs, wigs, bowls, and cups, with colors and combinations that stagger the imagination. This richly illustrated field guide examines how galls develop, and their uses, seasonal appearance and growth rate, predators, and defense mechanisms. The "architects" of galls--bacteria, fungi, mites, moths, beetles, flies, midges, and wasps--are explored in depth, and descriptions are paired with illustrations of these gall-inducing organisms and their typical galls. Gall accounts are divided into those that occur on trees, shrubs, and miscellaneous hosts, including native and ornamental plants. The guide contains a useful glossary and a section on literature cited.Looks at 536 gall species with 232 species not previously included in any field guideFeatures more than 120 species new to scienceExamines for the first time more than 90 species from southwestern oak treesContains more than 150 species from most of the deserts of the western states.